Sleep deprivation and suicide risk among minoritized US adolescents - Victoria A. Joseph; Noah T. Kreski; Katherine M. Keyes (BMC Psychiatry, 2023)
Abstract Objectives To assess (1) the prevalence of suicide ideation/behavior among adolescents with short sleep by race/ethnicity and (2) the association between sleep duration and suicidal ideation and behavior among American youth by race/ethnicity from 2007 to 2019. Methods Data were drawn from the Youth Risk Behavior Surveillance System (YRBSS). Logistic regression analyses were used to assess the relationship between sleep duration and suicidal ideation/behavior. Results Overall, suicide ideation/behavior increased among U.S. adolescents of all racial groups from 2007 to 2019. Adjusting for race/ethnicity, sexual identity, age, sex, substance use, trauma, and bullying, those with short sleep had approximately twice the odds [OR: 1.92 (95% CI: 1.65, 2.23)] of suicide ideation/consideration compared to those with long sleep. Stratified analyses indicated that Black students with short sleep had higher odds of making a suicide plan (OR = 1.51, 95% C.I.: 1.27, 1.79) compared with Black students with long sleep. A similar pattern was observed across other racial/ethnic groups (e.g., Hispanic: (OR = 1.74, 95% C.I.: 1.53, 1.97). Conclusion Emphasis on suicide interventions is of the essence, especially with increasing rates. Sleep duration significantly predicts suicide risk among all adolescents. Additional research is needed to assess factors that predict suicide among minoritized adolescents, specifically Black and Hispanic adolescents.